2013
DOI: 10.1021/jp404855s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Crystal Habit and Luminescence Properties of 4,4-Difluoro-1,3-dimethyl-4-bora-3a,4a-diaza-s-indacene, An Asymmetric BODIPY Dye

Abstract: The asymmetric substituted BODIPY dye 4,4-difluoro-1,3-dimethyl-4-bora-3a,4a-diaza-s-indacene crystallizes in three different crystal habits, that is, as needles (I), leaves (II), or microcrystalline sublimed crystals (III). All crystals share the same crystal structure but exhibit varying solid-state fluorescence from yellow-orange to deep red. The crystal structure mainly consists of one-dimensional chains of J-aggregates which leads to excitonic luminescence at λ = 600 nm. The point-dipole approximation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…In class A (aggregate), the decay of singlet excitons is again dominated by transfer to excimer-forming sites, but there is parallel transfer to distinct, strongly redshifted aggregates. Similar species are often attributed to BODIPY J-aggregates, 6,[12][13][14][15][16][17] but the observed time-resolved behaviour and temperature dependence reveal this to be an over-simplification. The states must be described specifically as J-coupled dimers, exhibiting exceptional near-unity quantum efficiency.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…In class A (aggregate), the decay of singlet excitons is again dominated by transfer to excimer-forming sites, but there is parallel transfer to distinct, strongly redshifted aggregates. Similar species are often attributed to BODIPY J-aggregates, 6,[12][13][14][15][16][17] but the observed time-resolved behaviour and temperature dependence reveal this to be an over-simplification. The states must be described specifically as J-coupled dimers, exhibiting exceptional near-unity quantum efficiency.…”
Section: Introductionmentioning
confidence: 65%
“…In the case of BODIPY dyes, it has been well documented in a wide range of derivatives that dispersion within a polymer matrix or deposition of pure films results in significant PL quenching accompanied by spectral shifts. 9,10,[12][13][14][15][16][17][18][19][20][21] Analogous effects have also been described in a wide range of covalent dimers, 11,15,[21][22][23][24][25][26] though the geometries are typically a poor match for the structures obtained in the solid state. Quenching in these systems is often attributed to the formation of non-emissive H-aggregates, identified by a broadening of the absorption spectrum at higher energies.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Effort has been put forward to tune the molecular packing through structural modification and thereby influence the solid state fluorescence output. [23][24][25][26][27][28][29][30][31][32][33][34][35] In this regard, small organic derivatives with olefin, acetylene, phenylenevinylene and phenyleneethynylene spacers have found current interest. 19,24,[36][37][38][39][40] Davis et al reported the solid state fluorescence of alkoxy-cyano substituted diphenylbutadiene derivatives.…”
mentioning
confidence: 99%
“…[9,10] The red shift of the observed fluorescencep resumably arises from reabsorption or aggregation. [21] For future medical or biological experiments, it is also crucial to test the cytotoxicity of the synthesized molecules. HUVEC isolated from human vessels served as am odel with utmost relevance for the human in vivo situation.…”
Section: Resultsmentioning
confidence: 99%